Long‐term effects of forest fire on habitat use by siamangs in Southern Sumatra. (22nd September 2020) - Lappan, S.; Sibarani, M.; O'Brien, T. G.; Nurcahyo, A.; Andayani, N.; Rustiati, E. L.; Surya, R. A.; Morino, L.
Abstract: Forest fires can cause direct mortality to wildlife, and the associated habitat damage can reduce carrying capacity and population densities. However, little is known about long‐term responses of animals to fire in the wet tropics. From 2000‐2015, we examined siamang ranging patterns in habitat damaged by fire to assess the effects on these arboreal frugivores. We mapped home ranges (HR) of seven siamang groups inhabiting contiguous HR 3‐5, 10‐12, and 17–18 years post‐fire. We predicted that if habitat connectivity or quality improved over time in burned areas, HR should become larger and centroid locations should shift toward recovering areas. Since territoriality constrains siamang ranging, we examined effects of social and habitat factors on ranging. By 18 years post‐fire, tree density in the burned area had returned to the 1997 baseline, but composite LandSat images indicated that tree species composition differed in burned and unburned forest. Our data and the associated models indicated that HR sizes in burned forest increased over time whereas those in unburned forest did not. Centroid locations moved little (15.5 ± 6.9 m y −1 ) and their movement appeared to be predominantly influenced by social factors, although HR centroids in burned habitat shifted further into the burned area while those in adjacent unburned forest did not. In a large burned area unused by siamangs before 2012, two new groups were observed 15‐17 years post‐fire, although one subsequently disappeared. This is the first study of the long‐term effects of fire on small ape habitat use. By 18 years post‐fire, siamangs had incorporated some burned areas into their HR, but did not use heavily damaged areas. Reduced frugivore densities in burned areas may inhibit forest regeneration by disrupting seed dispersal. Abstract : We examined siamang ranging patterns in habitat damaged by fire from 3 to 18 years post‐fire to assess the long‐term effects of fire on these arboreal frugivores. By 18 years post‐fire, siamangs had incorporated some burned areas into their home ranges, but did not use heavily damaged areas. Effects of the fire on siamang home range size and location were highly localized, suggesting that territoriality constrains their ability to adjust their movement patterns in response to changes in habitat quality.